2022
DOI: 10.3390/app122413018
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for Structural Health Monitoring and Damage Detection of Bridges: An Experimental Assessment

Abstract: The issue of monitoring the structural condition of bridges is becoming a top priority worldwide. As is well known, any infrastructure undergoes a progressive deterioration of its structural conditions due to aging by normal service loads and environmental conditions. At the same time, it may suffer serious damages or collapse due to natural phenomena such as earthquakes or strong winds. For this reason, it is essential to rely on efficient and widespread monitoring techniques applied throughout the entire roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For instance, it has been shown that the first few frequencies of a bridge, and in some cases even mode shapes, can be detected from smartphone and vibration sensors mounted in moving vehicles [77][78][79][80]. In this regard, in [80,81] vehicle vertical accelerations have been employed to identify the main frequencies of the Interchange 12 bridge in Dubai (UAE). In this case, the experimental set-up comprised both a single piezoelectric accelerometer (PCB-models 393B04) and an iPhone 11.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…For instance, it has been shown that the first few frequencies of a bridge, and in some cases even mode shapes, can be detected from smartphone and vibration sensors mounted in moving vehicles [77][78][79][80]. In this regard, in [80,81] vehicle vertical accelerations have been employed to identify the main frequencies of the Interchange 12 bridge in Dubai (UAE). In this case, the experimental set-up comprised both a single piezoelectric accelerometer (PCB-models 393B04) and an iPhone 11.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…However, the usage of OMA methods is not limited to the identification of structural systems, but it also includes other purposes such as performing a Structural Health Monitoring (SHM), the calibration of finite elements models and the detection of structural damages. OMA methods turned out to be extremely useful for real cases like historical buildings [6][7][8], bridges [8][9][10][11] and other type of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Once that the modal shapes have been estimated, the matrix containing all the analytical signals of the correlation functions, calculated as reported in equation ( 6), have been decomposed as in equation (10). The components on the diagonal of…”
mentioning
confidence: 99%
“…Moreover, since the structural input is due to the ambient vibrations (usually modelled as a white noise process [3][4][5]), OMA methods allow to identify the structural system when it is under operative conditions. This kind of methods have been used to identify structural systems [6][7][8], to perform structural health monitoring (SHM) [9][10][11][12][13], to calibrate finite elements models [14] and to detect structural damages [15,16]. OMA methods has been applied on historical buildings [7,17,18], tall buildings [19,20], bridges [21][22][23], masonry structures [24], dams [25], offshore platforms [26,27] and other structural systems [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%